COSEISMIC ANALISYS 2007 SIANOK EARTHQUAKE BASE ON GPS OBSERVATION FROM 1993-2007 - EFENDI (NIM: 25113008), JONI
Sumatra island is a part of Eurasian plate that has convergence interraction with Indo-Australian plate. Oblique subduction between those plates forming a subduction zone in the western part of the Sumatran island and fault segments onshore Sumatra island. Those subduction zones and fault segments often cause earthquakes in the region. Since the introduction of the Indonesia Geospatial Reference System 2013 (IGRS2013) as a geodetic datum for mapping activity in Indonesia, the change of reference frame position as a function of time due to the dynamics of the earth needs to be taken into account. The occurrence of two consecutive earthquakes on March 6, 2007 in the Lake Singkarak, West Sumatra (Sianok Earthquake), lead a coseismic deformation that affect the IGRS2013. In this study, an analysis performed to determine the most appropriate co-seismic deformation model of the Sianok earthquake and the extent of its impact on IGRS2013. Based on the analysis of validation residual value at 11 GPS stations, can be concluded that the most appropriate co-seismic deformation model of the Sianok earthquake is the model developed using earthquake parameter data derived from Global CMT with residual misfit 47.5 mm. The magnitude of the coseismic deformation does not affect the 1:1000 scaled map. However, it will affect the position (coordinate) of the sorounding Geodesy Control Network (GCN). So, the GCN coordinates must be updated.